(untitled) (International Seven Journal of Multidisciplinary, 2024)
Introduction: Hyper IgE syndrome (HIES) is a rare condition of the immune system characterized by various types of infections throughout life. This syndrome can be divided into two types, dominant heterozygous related to STAT3 gene mutation and recessive homozygous, which can also be subdivided into two groups related to Tyk2 and DOCK8 gene mutations, each presenting variations in their clinical presentations. Diagnosis is based on genetic sequencing, although there are some symptoms, clinical factors, and hereditary factors that can assist in diagnosis. There is no specific treatment for this pathology, with the main focus being on controlling infections and infusing immunological therapies such as intravenous immunoglobulin G.